Biochemical disorders of the skeleton - Smith, Roger, M.D (Postgraduate orthopaedics series., 1979)
Biochemical Disorders of the Skeleton explores the biochemical and clinical aspects of skeletal disorders, including osteoporosis, osteomalacia, Paget's disease of bone, osteogenesis imperfecta, and Marfan's syndrome. Homocystinuria, Ehlers-Danlos syndrome, mucopolysaccharidoses, hyperphosphatasia and hypophosphatasia, and fibrous dysplasia are also considered.